Contemporary perspectives in corporate social performance and policy : the Middle Eastern perspective - Stachowicz-Stanusch, Agata; Amann, Wolfgang (Emerald Publishing Limited : Information Age Publishing Inc., 2018)
The book Contemporary Perspectives in Corporate Social Performance and Policy - The Middle Eastern Perspective is our endeavor to deepen the current discussion about business and institutional activity in Middle Eastern countries and disseminate the new perspective of the scientific inquiry in the responsibility of various organization operating in this part of the world.The book is divided into four parts: "Introduction", "Reality and Challenges of Corporate Social Performance - The Middle Eastern Perspective", "Corporate Social Responsibility in Middle Eastern countries", "Corporate Social Performance -specific problems". There were included some theoretical and practical contributions into the topic of corporate social responsibility and corporate social performance based on experiences from different countries (such as Israel, Turkey, United Arab Emirates). We hope that this volume will help to understand better this specific region and its business activities.
Keywords: Social responsibility of business -- Middle East.; Business & Economics -- Development -- Economic Development.; Development economics and emerging economies.; elektronické knihy; electronic books